Factors associated with utilisation of dental services by the elders from São Paulo, Brazil. (22nd December 2020) - Soares, Gustavo Hermes; Ortiz‐Rosa, Ezequiel; Alves, Caroline Paula; Paz, Dayanne; An, Ki Sung; Pereira, Antonio Carlos; Biazevic, Maria Gabriela Haye; Frias, Antônio Carlos; Michel‐Crosato, Edgard
Abstract: Background: Population ageing in Brazil is rapid and is likely to place additional pressure over the Brazilian public health system. Objective: This study aims to examine the factors associated with utilisation of dental services in the previous year among a representative sample of older adults from São Paulo, Brazil. Methods: The sample included 5951 older adults who participated in the SBSP‐15 study, an epidemiological survey conducted in 2015 in the State of São Paulo, Brazil. The outcome "utilisation of dental services" was defined as having visited a dentist in the previous year. Chi‐square tests were employed in the bivariate analyses and Poisson regressions with robust variance in the multilevel analysis. Results: Only 30.5% of the participants had their last dental appointment within the previous year. Number of teeth and dental pain presented the strongest effects on the investigated outcome. Education, income, age, ethnicity, living alone, higher Family Health Strategy coverage and the Metropolitan area were associated with having visited a dentist in the previous year. Older adults who rated their oral health as positive did not report treatment need nor prosthodontic need, presented negative oral health‐related quality of life, had their last dental appointment in the public health system and sought treatment due to pain or extraction also were more likely to report the utilisation of dental services in the previous year. Conclusion: Regional, sociodemographic and subjective factors are associated with utilisation of dental services in the previous year among the elders from the State of São Paulo, Brazil.